Rethinking Hisbah and Sharia Proceduralism: A Comparative Approach to Justice in Contemporary Islamic Law - Mohamad Ridhuan Mohd Zawawi; Wafaa' Yusof; Zaini Nasohah; Anwar Fakhri Omar; Safiyyah Hannah Souit (Faculty of Sharia, IAIN Metro, 2025)
This study explores the impact of differences between the flexibility of the hisbah system in Islam and the procedural nature of the Syariah criminal enforcement system in Malaysia on the application of contemporary principles of justice. Using a qualitative approach, the research applies deductive content analysis based on primary and secondary sources, including classical Islamic legal texts, statutory laws, journal articles, books, and relevant websites. The data were analysed both descriptively and analytically, and the findings were presented thematically. To ensure data validity and reliability, the researcher used source triangulation. The findings reveal that contemporary justice principles—within the frameworks of hisbah and Syariah proceduralism in Malaysia—have not been applied comprehensively and holistically. Their implementation remains limited to specific areas and does not reflect a balanced integration of procedural, retributive, restorative, and distributive justice. While procedural justice appears to be better protected within the Syariah criminal enforcement system, this does not necessarily mean that justice is fully achieved, as gaps and inconsistencies still exist. In particular, retributive, restorative, and distributive justice require critical re-evaluation, as the procedural rigidity of the current system hinders their effective implementation—especially in terms of the severity and types of punishments imposed. In conclusion, this study highlights the need for reform in Malaysia’s Syariah legal framework. Such reforms may include codifying remand and raid procedures into procedural law, revising statutory sentencing limits, institutionalising restorative justice mechanisms, formally recognising mediation based on these principles, and introducing other necessary legal changes. This research contributes to strengthening the Syariah criminal justice system in Malaysia and promoting the more holistic application of justice principles.